Participatory predictors of users' satisfaction with housing infrastructure in Akure, Nigeria. Issue 13 (1st October 2018) - Fakere, Alexander Adeyemi; Folorunso, Clement Oluwole; Arayela, Olatunde; Adedeji, Yomi Michael
Abstract : Purpose: This paper is based on users' satisfaction with housing infrastructure as a derivative of their participation in evolving the facilities from inception. The paper aims to examine optimal performance of infrastructural facilities with a view to determine the satisfaction of users in the study area. Design/methodology/approach: This study reports on a cross-sectional doctoral research study on 304 household heads in the transitional and peripheral zones of Akure, Nigeria. The infrastructure studied were water supply, electricity supply, roads, drainage, waste management and security. A structured questionnaire, focus group discussions and physical observations were used. The data were analyzed using descriptive statistics, mean satisfaction scoring and categorical regression analysis. Findings: Respondents found the infrastructural facilities in their communities to be unsatisfactory; they also indicated low levels of participation in the provision of infrastructure. Residents were most satisfied with waste management and least satisfied with water supply. The results showed a significant relationship between users' participation and satisfaction with housing infrastructure. Practical implications: The findings imply that giving adequate attention to users' involvement in the provision process of infrastructural projects can enhance their satisfaction with infrastructure. Originality/value: The study highlights the benefits of involving users in the process of providing housing infrastructure, establishing a positive relation with their satisfaction.